Analysis of procedures used in achieving assists, their frequency and efficiency within handball games sustained Women's World Championship, Brazil 2011 - Balint, E. (Procedia - Social and Behavioral Sciences, 2014)
The study was focused on the frequency of application and efficiency of the assists used at the level of the team and players in a large- scale confrontation as the World Championship. Analysis of the main procedures of decisive engaging the players from the teams ranked in the top Women's World Championship in Brazil, 2011 and the level of efficiency throughout the official games held in the competition compared to the Romanian team. The flinging passes the highest percentage of frequency (51.3%), fact we give to the simplicity and naturalness of the flinging motion, procedure that is most common and mainly used throughout the game.